"Damned if you do, damned if you don't": Media frames of responsibility and accountability in handling a wildfire. (30th December 2019) - Nilsson, Sofia; Enander, Ann
Abstract: Previous research on media framing of wildfire has chiefly been concerned with the nature of wildfire in the context of climate change and with framing effects on policy and public opinion. Empirical studies on media content, hence what is mediated to crisis managers and the public concerning authorities' and the public's response, seem to be largely missing. This is remarkable, given that the media represent main sources of information that may influence crisis management and shape public opinion. Thus, the aim of this study was to identify key media frames relating to portrayals of public and authority responses during and after a wildfire crisis. The study is based on media articles from two time periods: immediately after the fire and 1 year later. We used a thematic method of analysis (TA), thus an inductive, "bottom‐up" approach. A core frame, Responsibility/accountability is identified, underpinned by two sub‐themes. One sub‐theme relates to the causes of the fire and its escalation, revealing a number of different interrelated blame frames. The second sub‐theme refers to management of the crisis, reflecting both authorities' and citizens' responses. The deficiencies of the former are implicitly suggested to have forced citizens to act to compensate for their inadequacy. The main theoretical contribution is the identification of an interrelationship between frames in relation to different groups of individuals responding to a crisis, pointing to a more complex view of framing effects. In addition, results show how media tend to assess crisis management based on idealistic criteria, inevitably making the evaluation negative. This contributes to an understanding of how media blame frames, thus "blame games, " may unfold. Practical implications of these results are discussed.